Deep Neck Contouring through the Ages - Su-Genyk, Peiyi; Quatela, Vito (Facial Plastic Surgery, 2024)
Deep neck contouring can achieve dramatic results in young and old patients. Both genetic predisposition and aging contribute to the malposition of deep neck structures and a poorly contoured neckline. Depending on the patient's anatomy, deep neck contouring should involve a combination of submental liposuction, platysmaplasty, subplatysmal fat lipectomy, resection of the anterior belly of the digastric muscle, and either cautery or resection of the submandibular glands. Resorption of the facial bony skeleton that occurs with aging affects the ultimate postoperative mandibular contour, and postoperative results thus differ in the young versus old patient. In patients in which there is concern for excess skin laxity, a concurrent facelift is necessary to excise excess neck skin. This article includes a discussion on how a combination of aging and genetics influence a patient's neck anatomy, critical preoperative considerations prior to performing deep neck contouring, intraoperative technique, and adjunct procedures that can further improve a patient's neckline.
Keywords: deep neck contouring; aging; platysmaplasty; digastric resection; submandibular gland; submental liposuction; facelift